Iron deficiency and athletic performance. (14th October 2021) - Csulak, E; Sydo, N S; Horvath, L H; Sydo, T S; Babis, B B; Mocsari, S Z M; Kaufmann, M K; Lakatos, B L; Kovacs, A K; Dohy, Z S D; Szabo, L S Z; Toth, A T; et al.
Abstract: Introduction: Iron metabolism determines the oxygen transport of the blood, thereby affecting the exercise capacity and performance. In patients with heart failure iron deficiency is a major risk factor that predicts and influences patient's quality of life. In athletes diagnosing iron deficiency is also extremely important as it determines sport performance. Purpose: Our aim is to study the correlation of iron metabolism parameters with exercise capacity in athletes. Methods: Cardiopulmonary exercise test (CPET) was performed as part of detailed sports cardiology screening. We studied in athletes the changes of iron metabolism parameters (serum iron, transferrin, total iron-binding capacity (TIBC), ferritin) and correlation with the exercise physiology parameters. Results: Our measurements were performed on 105 top athletes: swimmers (n=58, 55%; male = 29; junior = 30; 20, 4±4, 6 y), football players (n=47, 45%; junior = 6; 23, 2±5, 4 y). Laboratory test verified hemoglobin (male = 153, 8±9, 4; female = 141, 2±7, 7 g/L; p<0, 001) and hematocrit (male = 0, 45±0, 03; female = 0, 42±0, 02 L/L; p<0, 001) value in a normal range for all. In women, significantly lower ferritin (67, 8±76, 2 vs. 98, 9±48 μg/L; p<0, 05) and higher TIBC (78, 1±14, 3 vs. 66, 5±9, 3 μmol/L; p<0, 001) were observed. Young male athletes had significantly lower serum iron (16, 1±6 vs. 21, 2±7, 5 μmol/L; p<0, 05), ferritin (68±42, 7 vs. 109, 1±45, 5 μg/L; p<0, 01) and higher TIBC (76, 1±11, 0 vs. 64, 3±7, 4 μmol/L; p<0, 001) compared to adults. During CPET male athletes had higher maximal aerobic capacity (52.2±4.4 vs. 55.9±5.5 mL/kg/min; p<0.001) and ventilation (115.8±16.1 vs. 153.2±26 L/min; p<0.001) compared to females. Maximal aerobic capacity and ventilation showed positive correlation with ferritin (p<0, 0001). The ferritin cut-off value of iron supplementation was <100 μg/L. Iron supplementation was required in almost half of the athletes (n=49, 47%). Conclusion: Diagnosing iron deficiency in athletes, complete iron panel containing ferritin is required. According to our results iron status determines performance, therefore iron deficiency screening and iron supplementation is essential. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): - Supported by the ÚNKP-20-3-I New National Excellence Program of the Ministry for Innovation and Technology from the Source of the National Research, Development and Innovation Fund - The research was financed by the Thematic Excellence Programme (2020-4.1.1.-TKP2020) of the Ministry for Innovation and Technology in Hungary, within the framework of the Therapeutic Development and Bioimaging programmes of the Semmelweis University.